Validação da proteína MDP2 de Mycobacterium tuberculosis H37Rv como uma proteína intrinsecamente desordenada e geração de uma cepa nocaute para o gene hns - Abbadi, Bruno Lopes (2014)
The mycobacterial DNA-binding protein 2 (MDP2) of Mycobacterium tuberculosis is a small, basic protein known to bind to DNA in a non-specific manner and to anchor the nucleoid to the plasma membrane, promoting its unpacking. Motivated by a prior intrinsic disorder pre-diction in silico, we have used a complementary set of techniques to characterize this pro-tein, such as heat and chemical stability, gel filtration, limited proteolysis and electrophoret-ic mobility. Our results suggest that the MDP2 is structurally disordered, since it (1) was pre-dicted to be an IDP, having 86 % of its structure disordered; (2) resisted to denaturation in-duced by boiling temperature and to the chemical thrichloroacetic acid (TCA); (3) migrated anomalously on SDS-PAGE, appearing to be 1.4-fold higher its calculated molecular weight; and (4) was highly sensitive to proteolysis performed by proteinase K in comparison to glob-ular proteins. We also accomplished two experiments to determine the quaternary structure of the MDP2, such as gel-filtration and glutaraldehyde crosslinking. These two experiments showed that the protein has a tendency of self-aggregation, forming large clusters of pro-tein. We also performed the site-directed mutagenesis by allelic exchange in the hns gene, in order to develop a M. tuberculosis strain lacking the protein MDP2. The result of this knock-out showed that the hns gene is not essential for the survival of the mycobacteria, confirm-ing previous results performed by transposon mutagenesis. Combined with previous results related to MDP2 from other works, we speculate that this protein uses its highly disorder N-terminal region to bind to DNA through its KAAK and PAKK sequences in a non-specific man-ner. Thereby the MDP2 may act as a promiscuous protein inside the cell, binding to different regions of nucleoid by forming large clusters of proteins, in order to perform the DNA un-packing and to regulate several genes of the mycobacteria. We hope this work may contrib-ute to a better understanding of the mycobacterial metabolism, since the M. tuberculosis still stands a major global threat.